Practical tips for prevention of cardiovascular disease in women after quarantine for COVID-19 disease. - Mattioli, Anna Vittoria; Toni, Silvia; Coppi, Francesca; Farinetti, Alberto (Acta Biomedica Atenei Parmensis, 2020)
To contain the spread of CoV-19 / SARS-CoV-2 infection, several governments have imposed collective quarantine on the population. All of these restrictions have influenced women's health and induced an unhealthy lifestyle that, in some cases, could persist after the lockdown. The present commentary briefly analyzes the effects of quarantine on women’s lifestyle.Quarantine is associated with stress and depression, which lead to unhealthy nutrition and reduced physical activity, particularly in women. Unhealthy diet is usually poor in fruit and vegetables, with a consequent low intake of antioxidants and vitamins. However, vitamins have recently been identified as a weapon in the fight against the Covid-19. Some reports suggest that Vitamin D could exert a protective effect on such infection. In addition, women are less likely to engage in regular physical activity and have increased sitting time and sedentary behaviors during quarantine, which have led to weight gain. During quarantine strategies to increase home-based physical activity and to encourage adherence to a healthy diet have been implemented. Following quarantine, a global action supporting healthy Diet and physical activity is mandatory to encourage women to return to a good lifestyle routine.